Modeling Seismic Effects on a Stormwater Network and Post-earthquake Recovery - Biswas, Rahul R; Biswas, Tripti R (International Journal of Computer Sciences and Engineering, 2025)
This paper summarises the impact of earthquakes on Christchurch’s storm water network and the recovery strategies that are being applied to restore the performance of the network. Storm water hydraulic models are being used to determine the level of service in the storm water network, and the extent and severity of flooding pre- and post-quake for different extreme weather events. The modelling tools have been used extensively for land-drainage recovery works. To be suitable for use the storm water models must be sufficiently current and accurate to be a good representation of the actual operation of the storm water system. Thousands of earthquakes and earthquake aftershocks are continually changing the ground levels and the condition of different storm water infrastructure in Christchurch. The dynamic response of the surface water network and coastal plains due to earthquake-related topographical changes, lateral spreading, liquefaction, and subsidence posed a number of challenges for the local water authority. A case study on flood modelling for a flood-prone area of Christchurch has been reported in this paper. This paper outlines key challenges during the storm water model-building and updating process for a network which faces continual earthquakes and earthquake-related aftershocks.